BAKTI ANAK KETURUNAN TIONGHOA KEPADA ORANG TUA DI SMP PATRIA DHARMA KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI - Lova, Metra Lova; Natuna, Daeng Ayub Natuna Ayub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Formulation of the problem in this research is how high Consecrated children of Chinese descent in the District Patria Dharma Junior High Cliff Meranti Islands District. The purpose of this study was to determine the level of Consecrated children of Chinese descent in the District Patria Dharma Junior High Cliff Meranti Islands District. The benefits of this research can provide additional information to the parents about the efforts of parents to instill character values. This is a descriptive study with a quantitative approach. The population is 65 people. The samples in this study using a sample of Simple Random Sampling technique. The instrument used in this study was a questionnaire containing 60 items of the statement of Consecrated children of Chinese descent in the District Patria Dharma Junior High Cliff Meranti Islands regency, with the indicator 1) receive advice, 2) pleasing to parents, 3) do not precede the elderly, 4) please parents, 5) facing parents who fall into error, and 6) taking care of the elderly sick to death. Alternative answers each item has a statement strongly agree categories (SS) was scored 5, agrees (S) was given a score of 4, less amenable (KS) was given a score of 3, disagree (TS) was given a score of 2, and strongly disagree (STS) given a score of 1. The survey results revealed that the consecrated child of Chinese descent in the District Patria Dharma Junior High Cliff Meranti Islands District is very high. Keywords: Filial child to parents